A 10 year review of group B streptococcal infection among neonates admitted to Hospital Universiti Sains Malaysia - Ramli, Mohd Nor Hisham (2018)
Background: Group B Streptococcal (GBS) is a well-known cause of infections which causes significant morbidity and mortality in neonate. Neonates are primarily infected through vertical infections from a GBS colonized mothers. Intrapartum antibiotic prophylaxis during labour in a mother with risk has become the primary intervention in reducing the rate of transmission to neonates. This study aims to look at the numbers and clinical characteristic of early and late onset GBS infections in neonates with GBS admitted to Hospital USM. Objectives: To study the early and late onset GBS infections and its associated factors among neonates admitted to HUSM between January 2008 and December 2017. Methodology: A cross-sectional and retrospective record review study of neonates with Group B Streptococcal infection was conducted between January 2008 and December 2017. Early onset disease (EOD) was defined as GBS infection occurred in neonates aged within 7 days of life whilst late onset disease (LOD) occurred after 7 days of life. The positive cases of GBS were identified from the microbiology laboratory Hospital USM WHONET system database. The data on the proportions of neonates with GBS infection, EOD and LOD, and clinical characteristic and outcome were analysed through descriptive statistical analysis. The Chi-square and Fisher exact test were used to determine whether there were a significant difference of clinical presentations, laboratory parameters and duration of hospital stays in EOD and LOD. A p value less than 0.05 was considered significant in this study. Multiple logistic regression analysis was used to determine the association between maternal and neonatal factors toward early onset neonatal GBS. Results: A total number of 123 complete medical records review and data were retrieved. The findings show a total number of 111 (90.2%) neonates with early onset GBS infection and 12 (9.8%) neonates with late onset GBS infection. The age of neonates admitted ranging from day 1 to day 26 of life with a mean of 2.76 days. A majority of GBS cases were confirmed through urine GBS latex agglutination test with a total number of 68(55.3%) neonates and followed by blood culture with 24 (19.5%) neonates. 80 (65%) neonates were male neonates. Malay makes up 121 (98.4%) of the studied neonates. The neonatal weight 2.5 to 3.99 kg makes up majority of the cases with 89 (72.4%) neonates and most neonatal gestation ranging from 37 to 39 weeks with 63 (51.2%) neonates. A majority of the neonates delivered in the hospital and through vaginal delivery. A total of 67 (54.5%) mothers were between the ages of 21 to 30 years old with majority maternal parity of gravida 2 to gravida 5. Most cases were from district of Kota Bharu with 44.7% neonates followed by Besut 14.6% neonates and Bachok 13.8% neonates. From the record retrieved, only a total of 13(10.6%) mother screened for GBS via HVS and from that 7(5.7%) mother were positive for GBS. Intrapartum antibiotic prophylaxis (IAP) was only received by 4 (57.1%) mothers during delivery in those with positive GBS HVS screening. The most common clinical presentation in the early onset of GBS infection were sepsis, in 50 (45.0%) neonates followed by pneumonia in 31(27.9%) neonates and jaundice in 21(18.9%) neonates. However in late onset GBS infection, jaundice was the most common clinical presentation in 5(41.7%) neonates, followed by sepsis in 4(33.3%) neonates and fever in 3 (25.0%) neonates. A total of 61 (49.6%) neonates required some form of respiratory support with most of them needing oxygen support via nasal prong oxygen or headbox oxygen. Abnormalities of blood parameters only occur in the early onset of GBS neonatal infection group with leucocytosis was the most common laboratory abnormalities with a total of 24 (21.6%) neonates. CRP was only positive in a small number of cases with total of 23 (18.7%) neonates. The mean duration of hospital stay range between 1 day to 122 days with a mean of 14.15 days. Only 1 death was recorded whereby the baby was premature at 24 weeks with blood culture positive for GBS. Baby passed away at 19 hours of life. Through multiple logistic regression with various maternal and neonatal factors affecting the early onset group, it was noted that mothers with an increase of 1 year of age has a 0.89 the odds or 11% reduced risk or protection to have babies with early onset GBS. Conclusion: The majority of neonatal GBS infections were in the early onset of GBS group. The confirmation of GBS infection was mainly from urine GBS latex agglutinations test. The most common clinical presentation for early and late onset GBS infection were sepsis, pneumonia, jaundice and fever. Nearly half of the neonates with GBS infection require some form of respiratory support and hospital admissions more than 7 days. Increasing maternal age has become a protective factor in the early onset of GBS infection.